An Analysis Of Emotive Language Appeal On Flight Advertisement In Asia Week Magazine - Samsudin, Samsudin (2004)
This research is aimed at analyzing and describing the kinds of emotive language appeal that appear on flights advertisement in Asia Week Magazine. The problem of this research is what kinds of emotive language appeal that are in flights advertisement to persuade the readers. In this research, the writer uses a descriptive qualitative. The writer collects the flights advertisement in Asia Week magazine as the data. He applies a documentation methods in collecting data. The method is proposed to describe analytically the kinds of emotive language appeal in persuading the readers. He also conduct analyzing the data by (1) presenting, arranging and numbering data based on kind of emotive language, (2) analyzing the data based on type of emotive language and interpreted the persuasive power intended. The data source of the research are flights advertisement taken from Asia magazine from January - September 1998. Based on the result of analysis, the writer finds eight of emotive language appeal on flights advertisement in Asia Week magazine, they are rhetorical question, repetition, imperative, intensifier, figurative language, categorical statement and slogan. The advertiser uses that styles as a persuasive power to persuade the readers. Here, the advertiser chooses and uses some types of the style to affect the reader's feeling of a particular issue to make the readers are influenced and interested to use the product which offered.